Statistics for the behavioral sciences - Nolan, Susan A.; Heinzen, Thomas E. (New York Worth Publishers, 2012)
"Clearly written, this text makes statistics accessible to students by applying theoretical techniques to wide-ranging examples. Focusing on research design and statistical analysis, the revised second edition makes graphs easy to understand and offers guidelines on how to report results."--Publisher's description.
An introduction to statistics and research design -- Frequency distributions -- Visual displays of data -- Central tendency and variability -- Sampling and probability -- The normal curve, standardization, and z scores -- Hypothesis testing with z tests -- Confidence intervals, effect size, and statistical power -- The single-sample t test -- The paired-samples t test -- The Independent-samples t test -- Between-groups ANOVA -- Within-groups ANOVA -- Two-way between-groups ANOVA -- Correlation -- Regression -- Chi-square tests -- Nonparametric tests with ordinal data.
Keywords: Social sciences -- Statistical methods